IMPROVING THE DIAGNOSIS OF LEPTOMENINGEAL MALIGNANCY THROUGH AN INTERVENTION TO OPTIMISE CEREBROSPINAL FLUID COLLECTION. (29th November 2012) - Michael, B; Milburn-McNulty, P; Moxton, N; Fletcher, NA; Crooks, D
Abstract : Introduction: Leptomeningeal carcinomatosis is a rapidly progressive disease for which early diagnosis is vital. Cytological analysis of the cerebrospinal fluid (CSF) is the gold standard, however sensitivity is significantly impaired by inadequate volumes and delays in formulin fixation. Methods: We developed and disseminated a CSF cytology guideline pack, including a fixative bottle, with education sessions. We retrospectively identified all cytology analysis for 6 months before and after the introduction of the pack to assess the impact of the intervention. Results: We identified 83 and 66 patients before and after the introduction of the intervention respectively. After the intervention there was a significant increase in the median sample volume collected (4.2 ml and 6.7 ml respectively, p=0.0003) and the proportion with at least 10 ml collected (13 (16%) and 26 (39%), p=0.001) and the proportion fixed in formalin within 30 min (14 (17%) and 49 (74%), p=0.0001). There was also a trend towards a greater proportion of samples being suggestive or diagnostic of malignancy (9 (15%) vs 5 (6%) respectively, p=0.089). Moreover, if >6 ml was collected the OR of identifying malignant cells was 2.88 (p=0.01); if >10 ml was collected the OR was 3.87 (p=0.01). Conclusion: In conclusion the introduction of a simple CSF cytology pack and education sessions resulted in significant improvements in both the volume and fixation of CSF samples and was associated with a trend towards an increase in diagnostic sensitivity, which is critical for appropriate treatment.